2017
DOI: 10.1371/journal.pone.0169082
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Radiation-Induced Gastrointestinal, Bone Marrow Injury and Recovery Kinetics Using 18F-FDG PET

Abstract: Positron emission tomography using 18F-Fluro-deoxy-glucose (18F-FDG) is a useful tool to detect regions of inflammation in patients. We utilized this imaging technique to investigate the kinetics of gastrointestinal recovery after radiation exposure and the role of bone marrow in the recovery process. Male Sprague-Dawley rats were either sham irradiated, irradiated with their upper half body shielded (UHBS) at a dose of 7.5 Gy, or whole body irradiated (WBI) with 4 or 7.5 Gy. Animals were imaged using 18F-FDG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Together, these findings confirmed the work of multiple other investigators (e.g. Tang et al 2017;Li et al 2018) who have demonstrated that the irradiated hematopoietic system appears to fully recover within 1-2 months, with circulating blood counts, etc., returning to pre-exposure baseline levels. Nonetheless, some groups have reported delayed defects in the HSC compartment following TBI (e.g.…”
Section: Delayed (12 Week) Effects On Hematopoiesissupporting
confidence: 89%
“…Together, these findings confirmed the work of multiple other investigators (e.g. Tang et al 2017;Li et al 2018) who have demonstrated that the irradiated hematopoietic system appears to fully recover within 1-2 months, with circulating blood counts, etc., returning to pre-exposure baseline levels. Nonetheless, some groups have reported delayed defects in the HSC compartment following TBI (e.g.…”
Section: Delayed (12 Week) Effects On Hematopoiesissupporting
confidence: 89%
“…Another limitation of interim PET during CRT is the increased uptake of normal tissue, especially mucosa and gut. Preclinical and clinical studies have shown that there is a correlation between radiation-induced inflammation and FDG uptake [33][34][35] and FDG-PET is also used in several inflammatory diseases. 36 The increased normal tissue uptake hampers evaluation of tumor response and may have led to negative studies on response assessment in interim PET.…”
Section: Discussionmentioning
confidence: 99%
“…After a radiation dose of 50 Gy to the tumor, affected lymph nodes, safety margins, and elective lymph nodes, a consecutive boost of 4-16 Gy was prescribed to tumor/affected lymph nodes (average total dose: 58.9 Gy) with reduced margins. Concomitant chemotherapy consisted of two cycles of cisplatin (25 mg/m 2 /day, Days 1-3 and Days 29-31) and either paclitaxel (135 mg/m 2 /day, Day 1 and Day 29) or 5-fluorouracil (500 mg/m 2 /day, Days 1-5 and Days [29][30][31][32][33].…”
Section: Patients Treatment and Follow-upmentioning
confidence: 99%
“…Most tumors and inflammatory lesions lesion have increased uptake of 18 F-FDG owing to enhanced glucose utilization [29,37]. More recently, several studies have examined the ability of 18 F-FDG uPET-CT imaging to assess radiation damage [38,39]. This study noted a prominent increase in signal in the radiation-alone group that was dramatically reduced with PBM treatments.…”
Section: Discussionmentioning
confidence: 92%